Patients', radiographers' and radiography students' experiences of 360° virtual counselling environment for the coronary computed tomography angiography: A qualitative study. Issue 2 (May 2021) - Paalimäki-Paakki, K.; Virtanen, M.; Henner, A.; Nieminen, M.T.; Kääriäinen, M.
Abstract: Introduction: The aim of this study was to describe patients', radiographers' and radiography students' experiences of the developed 360° virtual counselling environment (360°VCE) for the coronary computed tomography angiography (cCTA). Methods: A descriptive qualitative approach was used. The participants were cCTA patients (n = 10), radiographers (n = 10) and radiography students (n = 10) who used the 360°VCE and visited or worked at a university hospital in Finland. The 360°VCE, resembling the authentic environments of a CT imaging unit, included digital counselling materials in text, image, animation and video formats. Data were gathered through thematic interviews individually to obtain an understanding of participants' perspectives and analyzed by inductive content analysis. Results: Five main categories and 15 categories were identified. Identified benefits of the 360°VCE for patients included improvements in knowledge, spatial and environmental orientation,  and senses of security and self-efficacy,  with reductions in fear and nervousness. Patients found the counselling materials engaging,  and that the 360° technology conveniently provided reassuring familiarity with the environment before their visit. Identified benefits for radiographers and radiography students included improvements in patients' mental preparedness,  knowledge,  spatial and environmental orientation,  and reductions in patients' fear, which eased procedures and enhanced diagnostic success. The 360°VCE also provided useful information and familiarization with the cCTA unit for students during clinical practice and staff of referring units.  Conclusion: It seems that patients', radiographers' and radiography students' experiences of 360°VCE respond to patients' needs by improved knowledge and reduced fears. Thus, current counselling practices can be usefully complemented with spherical panoramic imaging technology and online information delivery. Implications for practice: The results may be used to improve patient counselling and care, thereby optimizing the cCTA examination procedure and reducing fear. However, further research is needed to characterize experiences of the 360° VCE more comprehensively.